IMPLEMENTASI CUSTOMER RELATIONSHIP MANAGEMENT (CRM) PADA PENJUALAN ONLINE DI TOKO UTAMI - Muhamad Hadi Al Gifar; muhsin mkom (FKOM UNIKU, 2016)
The main store is a company that sells furniture items from the manufacturer to the customer. To be able to attract and improve customer service needed a strategy in an effort to create relationship between main store with customer known as Customer Relationship Management (CRM), application of crm operational at main store that is on service process, marketing and sales. online sales system in main store is built using waterfall system development method. Tools for design using flowmap, context diagram, DFD, and ERD. While the programming language using PHP and for the database using MySQL. Implementation of CRM in this system is the service in getting information and facilitate the purchase, delivery and submission. So the purpose of the implementation of CRM on this sales system can be achieved. The final stage of designing the sales system at Toko Utami by applying the CRM method is to test the system created using blackbox and whitebox testing. Value added from making this application to facilitate Store Utami do marketing or promotion to customer. With this system is expected to facilitate customers to obtain information about the products - products sold in Toko Utami and able to facilitate the booking anytime and anywhere